Sporen van stadhouders: Verblijven en besturen in het westelijke deel van het Binnenhof (Bulletin KNOB, 2022)
In anticipation of the current major restoration of the Binnenhof, the home of the Dutch parliament, building historians conducted research into this historically important complex of buildings in The Hague. This article focuses on the western part of the complex and the role played there by the stadholder and the States of Holland. In the northwest corner of the Binnenhof, an L-shaped Knights’ House arose in the middle of the fourteenth century with a residence for the stadholder on the first floor while the ground floor was used by the States of Holland.In 1585 Prince Maurits took up residence in this part of the Binnenhof and to underline his status had a tower built on the northwest corner (completed 1604). Later he had his accommodation expanded (1620-1621). His successor Frederik Hendrik further expanded the accommodation with an extruded corner containing private quarters for his son William’s wife (Mary Stuart). With the death of William II in 1650, the first stadholderless period (1650-1672) began. The States of Holland seized on this opportunity to reinforce their claim to the buildings by demolishing part of the recent expansion on the Hofvijver side and building a prominent new meeting place.As a consequence of the war with the French in 1672, William III became stadholder and to compensate for the lost space he commissioned an expansion of the complex on the south side (1677-1678). After the death of his wife Mary II Stuart, he had a stately house built for his favourite, the 1st Earl of Albemarle, on the south edge of the Prinsentuin in circa 1695. William’s death in 1702 ushered in the second stadholderless period until the threat of war in 1747 led to the appointment of William IV as stadholder. At this point the accommodation at the Binnenhof was deemed to be too small for the court and plans for a new palace were drawn up. What his father had been unable to achieve, William V accomplished. Existing buildings in the southwest corner made way for new stadholder quarters, but not until the States of Holland had built a new Comptoir-Generaal (money office) a little further away in 1777. In 1779 work on new quarters commenced. They consisted of a representative section in the Binnenhof, an apartment for the stadholder with an entrance on the Buitenhof and a service wing – the Cingelhuis – on the south side. The latter replaced the service wing of the Court of Albemarle. The new accommodation was finished by 1792, but just three years later William V was forced into exile, after which the newly formed Batavian Republic turned the ballroom into a meeting room, which served as the chamber of the House of Representatives from 1814 to 1992. The chamber of the States of Holland has been in use by the Senate since 1849.